The Fate of a Digital Slate: Unexpected Issues with Deployment in Rural India - Thies, Indrani Medhi; Tewari, Anuj; Jain, Mohit; Cutrell, Ed (User Experience Magazine, 2012)
As many UX professionals know, an initial rosy impression about the usability of a system may be trumped by unexpected issues seen in the context of actual deployment. These kinds of surprises can be especially dramatic when working in the area of ICT4D (Information and Communication Technology for Socio-Economic Development). We describe a case study of the deployment of a prototype low-cost digital slate for assisting the tracking of child malnutrition in rural India. Our prototype uses an ink pen and normal paper coupled with an interactive touch screen that allows for a fairly seamless transition from older, paper-based systems to the recording of digital information. This was designed for people who have little or no experience working with digital systems beyond simple cellular phones or calculators. In previous explorations, we had tested the slate with low-income, low-literate users in a rural microfinance setting. There, we found the slate to be very effective, winning the approval of both our users and NGO partner. Following this result, we adapted the device to a health data record management application for child malnutrition tracking. In the initial training and evaluation of the system with 10 low-income, low-literate, rural health workers in central India, it looked like an unqualified success. However, in a 3 month follow-up field trial with the same users, we encountered a number of unexpected challenges that overwhelmed our initial optimism. This experience demonstrates that we must pay a great deal of attention to issues well beyond simple usability to broader socio-technical concerns that arise in situating these systems into real-world settings.